The Social Cognitive Theory Model in Predicting Maternal Behavior for Healthy Child Development in Yogyakarta Indonesia - Nursanti, Ida; Murti, Bhisma; Mulyani, Sri (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2025)
Early childhood development determines the quality of future generations. A mother is crucial in encouraging a child’s growth and development. This research aims to determine the influence of social psychological factors that influence maternal behavior on healthy child growth and development using the Social Cognitive Theory (SCT) model. This cross-sectional study was conducted from July to October 2023 in Yogyakarta, Indonesia. A sample of 400 mothers with children under five (12-59 months). The dependent variable is the maternal behavior in child development, and the independent variables are observational learning, outcome expectations, self-efficacy, and family support. All variables were measured by questionnaire, and the data were analyzed by path analysis using Stata 13 statistical software. A maternal’s behavior is directly and positively related to observational learning (b= 0.28, p<0.001), outcome expectations (b= 0.24, p<0.001), self-efficacy (b= 0.37, p<0.001), and family support (b= 0.09, p=0.005). The goodness of fit path analysis indicates p > 0.05, RSME< 0.001, TFI= 1.00, TLI= 1.00, and SRMR< 0.001. A maternal’s behavior is directly and positively related to observational learning, outcome expectations, self-efficacy, and family support. Interventions to improve mothers’ healthy behavior in accelerated child development should prioritize efforts to increase self-efficacy.